Theatre world : critical perspectives on Greek tragedy and comedy : studies in honour of Georgia Xanthakis-Karamanos - Fountoulakis, Andreas, 1969-; Markantonatos, Andreas; Vasilaros, Geōrgios (Trends in classics. Supplementary volumes., 2017)
This collection of essays, published in honour of Professor Georgia Xanthakis-Karamanos, addresses topics which lie at the forefront of current research on the fields of Greek drama and classical reception studies. It brings together internationally disti.